DIALOGUE NORD-SUD : ETUDE DE L’ACTE D’ENONCIATION DANS LE DISCOURS DU PRESIDENT PAUL BIYA AU SOMMET MONDIAL A COPENHAGUE - Jean Paul BALGA (Diversitate si Identitate Culturala in Europa, 2010)
This article aims at analyzing the paths of the North and the South, in the context of the critical situation. We will conduct a case study through the means of an emblematic figure of the political scene in Central Africa: His Excellency Paul Biya. We will put forward his powerful speech delivered on December the 17th in Copenhagen at the World Summit on Climate Change. The President of the Republic of Cameroon distinctively made heard the voice of the black continent in the international forum at a global level. The commitment of the speaker is revealed especially in speech acts; the utterance system chosen by the speaker is rich and varied: deictics, personal pronouns, demonstratives, temporal locations, terms of statement and enunciation are heavily involved in the Head of the State’s determination, who sees himself as being Africa’s lawyer; for the African leader, language represents an agile way of action: „saying is doing”.